The Effect Of Training Programs On The Performance Of Employees At Bank Kalbar Main Branch In Pontianak Mediated By Intrinsic Motivation And Work Experience - Febriadi , M Alfin; Daud , Ilzar; Irdhayanti , Efa; Hendri , M Irfani; Fahruna, Yulyanti (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The This study aims to examine and analyze the effect of training programs on employee performance at Bank Kalbar Main Branch Pontianak, mediated by intrinsic motivation and work experience. A quantitative approach was used with a questionnaire method involving 115 employees selected using a simple random sampling technique. Data analysis was conducted using SmartPLS version 4.1.0.9 with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Descriptive results show that respondents' perceptions of the variables training, intrinsic motivation, work experience, and employee performance are positive, indicating a significant contribution in supporting employee performance. The findings indicate that the training program has a positive and significant effect on intrinsic motivation, the training program has a positive and significant effect on work experience, and the training program has a positive and significant effect on employee performance. Intrinsic motivation has a positive and significant effect on employee performance, and work experience also has a positive and significant effect on employee performance. The training program has a positive and significant effect on employee performance mediated by intrinsic motivation, and it also has a positive and significant effect on employee performance mediated by work experience. This research provides insights into the importance of training programs as a factor influencing employee performance at Bank Kalbar Main Branch Pontianak.